The Prognostic Value of Preoperative Serum D-dimer Levels After Surgical Resection of Thymic Epithelial Tumors. (16th September 2022) - Huang, Yang-Yu; Liu, Xuan; Liang, Shen-Hua; Hu, Yu; Ma, Guo-Wei
Introduction: Thymic epithelial tumors are the most common mediastinal tumors. Despite the high survival rate after surgery, some patients still require postoperative adjuvant therapy and closer follow-up. Hematological indicators such as biochemical routines and coagulation indicators have been reported to be independently associated with the prognosis of various malignancies. Therefore, we included hematological indicators in the analysis. Methods: The data of 105 patients with thymic epithelial tumors were retrospectively collected from Sun Yat-sen University Cancer Center, and the patients with missing preoperative hematological indicators were excluded. X-tile software was used to obtain the best cutoff value of each preoperative hematological indicator, and COX regression analysis and Kaplan-Meier survival curves were used to demonstrate statistically significant results. Results: COX univariate regression analysis of all patients showed that Masaoka stage, T stage, WHO histologic types, D-dimer, albumin-fibrinogen ratio (AFR), Fibrinogen (Fbg) were associated with postoperative overall survival ( P < .05). T stage, WHO histologic types, D-dimer, and AFR were associated with postoperative recurrence-free survival ( P < .05). Finally, multivariate regression analysis showed that T stage, D-dimer levels were independently associated with postoperative overall survival (OS) and recurrence-free survival (RFS) in patients with thymic epithelial tumors. Conclusions: For thymic epithelial tumors, higher preoperative D-dimer levels predict poorer survival and shorter recurrence-free survival. This may help guide postoperative adjuvant therapy and follow-up patterns in patients with thymic epithelial tumors.